"Like Upgrading From a Typewriter to a Computer": Registered Reports in Education Research. (April 2020) - Reich, Justin; Gehlbach, Hunter; Albers, Casper J.
Registered reports engender a review process in which reviewers evaluate the merits of the research question rather than the magnitude or direction of the results. In this process, authors first submit introduction, methods, and prespecified analyses sections of an article. Next, an initial peer-review process assesses the merits of the research question, in the absence of knowing the results. Worthy articles are granted an "in-principle acceptance." The authors, then conduct their study, analyze their data, write up the remainder of their article, and resubmit it. The in-principle acceptance means that if the authors adhere to the research design as originally submitted, then the article will be accepted. Building from seven of the earliest registered reports in education research, our introduction describes the benefits, opportunities, and challenges of registered reports as a means to increasing transparency in research and reducing the number of illusory results.